1985
DOI: 10.1172/jci112042
|View full text |Cite
|
Sign up to set email alerts
|

Serial studies of autologous antibody reactivity to melanoma. Relationship to clinical course and circulating immune complexes.

Abstract: The low titer and incidence of autologous antibody to melanoma has hampered its evaluation. Through acid dissociation and ultrafiltration of serum, we have been able to augment the autologous immune response in 9 of 10 patients studied. This result suggests that autologous antibody is present in most patients with melanoma, but is obscured by circulating antigen and the formation of immune complexes. Because native antibody and antibody derived from circulating immune complexes are produced by the host against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
9
18
0
Order By: Relevance
“…The etiology of the first two drops is not clear but may be the result of treatment with surgery and radiotherapy, respectively. The third drop in antibody titer may be due to treatment with interferon as has been reported previously (22). Of additional note is the preterminal rise in both native (PRE) and AD&U (POST) antibody titers.…”
Section: Isolation Ofmelanoma Antigenssupporting
confidence: 59%
See 4 more Smart Citations
“…The etiology of the first two drops is not clear but may be the result of treatment with surgery and radiotherapy, respectively. The third drop in antibody titer may be due to treatment with interferon as has been reported previously (22). Of additional note is the preterminal rise in both native (PRE) and AD&U (POST) antibody titers.…”
Section: Isolation Ofmelanoma Antigenssupporting
confidence: 59%
“…We have previously reported that this technique is successful in enhancing autologous antibody reactivity in 9 of 10 cases studied (20,22). Serial studies of autologous antibody reactivity, in native and dissociated sera, have demonstrated correlations between clinical course and disease progression (22). In addition, we have found that the presence host-derived antibody reactivity against an allogeneic melanoma cell line is a predictor of eventual disease recurrence (23).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations